An exploratory study on the usefulness of intellectual capital information: academic' perception - Abdulrahman Anam, Ousama; Abdul Hamid, Fatima; Abdul Rashid, Hafiz Majdi (Inderscience, 2011)
Abstract: In the knowledge economy; companies are depending more on intellectual capital(IC) to create values. IC is considered as the intangible resources that help in value creation of the company. IC consists of three categories: internal capital (INC), external capital (EXC) and human capital (HUC). The paper aims to examine the academics’ perception of the usefulness of IC information disclosed in the annual reports of Malaysian listed companies. The primary data were collected by a questionnaire survey. The statistical techniques which were conducted to analyze the data are descriptive statistics and one sample t-test. The paper found that the academics were perceived IC information (i.e., overall) disclosed in the annual reports to be useful for the purposes of decision making. In addition, the findings showed that the mean of the perception of the usefulness of EXC information is higher compared to the means of INC and HUC. In addition, the findings of the t-test reveals that the perceptions of IC information (i.e., overall), INC information, EXC information and HUC information are statistically significant. These findings are interesting because if Malaysian listed companies understand the information needs by various users, then the companies would disclose more IC information that can satisfy the users’needs and enhance transparency in the capital market.